PENCEGAHAN FRAUD PENGELOLAAN KEUANGAN DESA (STUDI KASUS KECAMATAN UTAN KABUPATEN SUMBAWA) - Fadli Faturrahman (JURNAL CAFETARIA, 2023)
This study aims to determine the effect of internal control systems, accountability and organizational ethical culture on fraud prevention in village financial management in Utan District, Sumbawa Regency. The method used is quantitative with a descriptive approach. The data source used is primary data collected by distributing questionnaires. In this study using data analysis techniques, namely data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the internal control system and organizational ethical culture have no effect on fraud prevention, this is due to the fact that some village governments have not implemented proper separation of powers and duties due to a lack of human resources. As well as the ethical culture of the organization also has no effect on fraud prevention. While accountability has an effect on fraud prevention, this means that all village administrations understand the importance of understanding and applying the concept of accountability because fraud prevention can start from a lack of accountability and internal control.